Managing Employee Performance of Sharia Banking through Religiosity and Islamic Work Ethics in the Covid-19 Pandemic - Darmastuti, Ismi (The journal of contemporary issues in business and government, 2022)
The Covid-19 pandemic has spread to various countries, including Indonesia. As a result, almost all sectors experienced contraction, including Islamic banking. However, Islamic banking is considered quite capable of surviving this impact based on the empirical facts of the previous crises. The purpose of this study is to analyze how the performance of employees in Islamic banking during the Covid-19 pandemic. In this case, Islamic banking is required to be able to develop even though it is during the Covid-19 pandemic. This research was conducted in Islamic banking companies, especially in West Java. The sample used is employees who have worked for a minimum of two years using nonprobability sampling techniques. The analytical tool used is Structural Equation Modeling (SEM). By conducting this research, it is hoped that it will be able to contribute to the company with policies as an effort to manage Islamic banking employees during the Covid-19 pandemic in order to stick to the guidelines of the Koran and Hadith and to contribute to existing knowledge.